Nursing evaluation during treatment with helmet continuous positive airway pressure in patients with respiratory failure due to COVID-19 pneumonia: A case series. Issue 1 (January 2022) - Privitera, Daniele; Capsoni, Nicolò; Mazzone, Annamaria; Airoldi, Chiara; Angaroni, Laura; Pierotti, Federico; Rocca, Eugenia; Dal Molin, Alberto; Bellone, Andrea
Abstract: Background: During COVID-19 outbreak, with the increasing number of patients presenting with acute respiratory failure, a large use of non invasive positive pressure ventilation was done in the emergency departments and medical wards despite the lack of recommendations. Objectives: This study describes the clinical characteristics of patients presenting to the hospital with acute respiratory failure due to COVID-19 related pneumonia undergoing treatment with helmet continuous positive airway pressure (CPAP) with a strict nursing evaluation and monitoring. Methods: A case series study enrolling adult patients admitted to an emergency department of an Italian hospital with acute respiratory failure due to COVID-19 pneumonia from March 18th to April 18th, 2020, was conducted. Only patients who strictly followed a local CPAP protocol were enrolled. Results: A total of 52 patients were included in this study. Thirty-eight patients (73%) were judged eligible for endotracheal intubation (ETI). Eighteen (34.6%) were intubated. Sixteen (30.8%) patients died: seven (38.9%) and nine (26.5%) in the eligible-for-ETI and non eligible-for-ETI group, respectively. The median hospital length of stay was different in the ETI and non-ETI group: 26 days (interquartile range [IQR]: 16–37) vs 15 days [IQR 9–17] (p = 0.005). The median invasive mechanical ventilation time was 11 days [IQR 7–21] with an ICU length of stay of 14.5 days [IQR 10–28]. During the CPAP trial, among patients eligible for ETI variations over time for positive end-expiratory pressure (p = 0.003) and respiratory rate (p = 0.059) were found between intubated and non-intubated patients. Conclusions: A short closed monitored CPAP trial could be considered for acute respiratory failure due to COVID-19 pneumonia before considering ETI. A progressive positive end-expiratory pressure titration should target reduction in a patient's respiratory rate. More studies are needed to evaluate the efficacy and predictors of failure of CPAP and non-invasive positive pressure ventilation in patients with acute respiratory failure due to COVID-19 pneumonia.